The Inactivated gE/TK Gene-Deleted Vaccine Against Pseudorabies Virus Type II Confers Effective Protection in Mice and Pigs - Jin, Yu-Lan; Yin, Di; Xing, Gang; Huang, Yan-Ming; Fan, Chun-Mei; Fan, Cheng-Fei; Qiu, Xiao-Huo; Dong, Wei-Ren; Yan, Yan; Gu, Jin-Yan; Zhou, Ji-Yong (Frontiers in Microbiology, 2022)
The highly virulent and antigenic variant of pseudorabies virus (PRV) emerged from classical Bartha-K61-vaccinated pig herds has caused substantial economic losses to the swine industry in China since 2011. A safe and more effective vaccine is most desirable. In this study, a gE/TK gene-deficient PRV, namely HD/c, was constructed based on a PRV type II DX strain isolated from a commercial vaccine immunized farm and the HD/c-based inactivated vaccine was formulated and evaluated for its safety, immunogenicity and protective efficacy in mice and piglets. The resulting PRV HD/c strain has similar growth curve to the parental DX strain. After vaccination, the inactivated HD/c vaccine did not cause any visible gross pathological or histopathological changes in the tissues of mice and piglets, and provided rapid and potent protection against the challenge of the classical and variant PRVs at day 21 post-vaccination in mice. A single immunization of 108.5TCID50 inactivated PRV HD/c strain elicited robust immunity with high titer of neutralizing antibody and provided complete protection from lethal challenge of PRV DX strain in piglets. These results indicated that the inactivated PRV HD/c vaccine with the deletion of gE/TK genes was a safe and effective PRV vaccine candidate for the control of PRV.